Preparation and characterization of nano composites from metal oxides and activated carbon from banana peel (MO@BPAC, MO=NiO, CuO and ZnO) for 2 nitrophenol removal from aqueous solutions - Ahmah Rafat; Saeedeh Hashemian; Masoud Reza Shishabor (Heliyon)
In this research, activated carbon from banana peel (BPAC) was prepared by calcination (600 °C) method. Nano composites MO@BPAC (MO=NiO, CuO and ZnO) were prepared and then were characterized by XRD, FTIR, FESM, EDX, BETand TGA methods. Formation of MO@BPAC nanocomposites was confirmed by analysis methods. The XRD patterns showed formation of nanocomposites did not change crystalline phase of metal oxides. TGA analysis also showed the MO@BPAC had high thermal stability to 780 °C. Removal of 2-nitrophenol by MO@BPAC nanocomposites was studied. The optimum contact time of 80 min for NiO@BPAC, 100 min and 120 min for ZnO@BPAC and CuO@BPAC was observed. The order of percent removal of 2-nitrophenol by nanocomposites was as follow: NiO@BPAC > CuO@BPAC > ZnO@BPAC. The maximum removal of 2-nitrophenol 40 mg L−1was attained at pH 9 and sorbent dose of 0.12 g. The kinetic studies showed adsorption of 2-nitrophenol was described better by pseudo second order kinetic model than pseudo first order kinetic. The studies for equilibrium data showed Langmuir isotherm model gave better correlation with the experimental data (qe = 303 mg g−1 for NiO@BPAC). Thermodynamic parameters indicated adsorption of 2-nitrophenol by MO@BPAC nanocomosites were spontaneous and endothermic. The NiO@BPAC could be reused fourth cycles.